An Underlying Pathological Factor in Pancreatic Cancer and Diabetic Retinopathy: A High-level Over-expression of N-and O-glycan Glycosyltransferases in Pancreatic Tumors and Diabetic Neutrophils - E. V. Chandrasekaran; Sriram Neelamegham; Khushi L. Matta (Current Advances in Chemistry and Biochemistry Vol. 5, 2021)
Diabetes is a widely existing disease in patients at risk of pancreatic cancer. It originates from pancreatic endocrine gland whereas pancreatic cancer develops from exocrine glands. Leukocyte cell surface glycans are involved in leukocyte-endothelial cell adherence and retinal endothelial cell death in diabetic retinopathy. A stimulation of hexosamine biosynthesis pathway occurs in diabetes and in pancreatic cancer controlled by oncogene KRAS variant. The present study found a significant elevation of \(α\)1-3 and \(α\)1-4fucosyltransferase activities in pancreatic cancer serum. We examined 5 pancreatic non-tumor and 14 pancreatic tumor tissue specimens for quantitative changes in glycosyltransferse (GTs) activities in pancreatic tumorigenesis by following the incorporation of 14C or 3H monosaccharide (CPM) from 14C or 3H monosaccharide donors into specific acceptor catalyzed by 1 mg protein of TritonX-100 solubilized tissue extract. As compared to pancreatic non-tumor tissue specimens with a very low level of GTs activities, pancreatic tumor specimens on average contained 26.0, 42.9, 331.7, 121.0 and 62.8-fold of \(α\)1-2, \(α\)1-3, \(α\)1-4, \(α\)1-6 FTs and FT VI activities respectively. The major sialyltransferase \(α\)2-3 (O)ST and sialomucin glycoproteins increased 95.4 and 4.0-fold; N-glycan \(α\)Man: \(β\)1-2GlcNAc-T, chain elongating \(β\)Gal: \(β\)1-3 GlcNAc-T and N-glycan GalNAc capping \(β\)1-3/1-4 GalNAc-T were respectively 95.0, 2.7 and 14.8-fold and the mRNAs of FUT-4, \(β\)1-3 and \(β\)1-4 GalNAc-Ts were 8.3, 12.0 and 2.4-fold respectively. The increase in activity in neutrophils of retinopathy vs. normal was: \(β\)1-2- GlcNAc-T (9.0 fold), \(β\)1-3-GlcNAc-T (2.5), \(α\)1-3- FT (3.5), \(α\)1-6-FT (3.3), FTVII (1.9), \(α\)GalNAc: \(β\)1-3-GalT (1.4), \(β\)GlcNAc: \(β\)1-4-Gal-T (2.1), \(α\)2-3-(O)ST (2.1), \(α\)2-3-(N)ST (4.5), \(α\)2-6-(N)ST (8.1). GalNAc replacing Gal in LacNAc terminals results in changes of glycosyltransferase specificities and the modified GalNAc \(β\)1-4GlcNAc by FTs and STs bind to lectins such as WGA and SNA. In contrast to a low-level expression-difference of glycosyltransferases between tumor and non-tumor specimens from stomach, prostate and colon, a multifold increase in GTs in pancreatic tumor would indicate their significant role in invasion and intractability of pancreatic cancer. The high-level GT activities in diabetic neutrophils could contribute to the alterations in cell-cell interactions in diabetic retinopathy.